An exploration of vibration based damage detection techniques for composite materials - Pathan, Firoj Umraobhai; Patil, Milind M.; Baviskar, Prasad; Aher, Vishnu S. (Zielona Góra: Uniwersytet Zielonogórski)
Structural damage monitoring is inevitable for the structures to perform during their intended service life adroitly. In the present review, literature related to techniques for diagnosing vibration-intensive damages have been evaluated in order to determine the material characteristics, such as stiffness and damping.
Keywords: composite materials; damage detection; vibration analysis; structural health monitoring; artificial neural networks